2012
DOI: 10.1371/journal.pone.0033509
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Production of Bio-Isoprene Using Hybrid MVA Pathway and Isoprene Synthase in E. coli

Abstract: The depleting petroleum reserve, increasingly severe energy crisis, and global climate change are reigniting enthusiasm for seeking sustainable technologies to replace petroleum as a source of fuel and chemicals. In this paper, the efficiency of the MVA pathway on isoprene production has been improved as follows: firstly, in order to increase MVA production, the source of the “upper pathway” which contains HMG-CoA synthase, acetyl-CoA acetyltransferase and HMG-CoA reductase to covert acetyl-CoA into MVA has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
135
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 36 publications
(47 reference statements)
0
135
1
Order By: Relevance
“…2A). The strain expressing the L. casei enzymes produced 50% more mevalonate than other engineered E. coli strains described in previous work (30)(31)(32).…”
Section: Construction Of a Nonnatural Metabolic Pathway For Biosynthementioning
confidence: 81%
“…2A). The strain expressing the L. casei enzymes produced 50% more mevalonate than other engineered E. coli strains described in previous work (30)(31)(32).…”
Section: Construction Of a Nonnatural Metabolic Pathway For Biosynthementioning
confidence: 81%
“…Isoprene is a platform chemical for a variety of products, but it is mostly employed in the production of synthetic rubber [24][25][26] . The isoprenoid pathway also provides precursors for over 25,000 known biomolecules including drugs such as taxol and potential biofuels 27 .…”
mentioning
confidence: 99%
“…The isoprenoid pathway also provides precursors for over 25,000 known biomolecules including drugs such as taxol and potential biofuels 27 . There have been a number of efforts to produce isoprene in microorganisms 24,26,28,29 and the best reported yield is 28% from glucose 24 . We recently showed that a synthetic biochemistry system could produce isoprene in 495% yield from pyruvate as long as high-energy cofactors were added 30 .…”
mentioning
confidence: 99%
“…Engineered E. coli strain, YJM25 was used during isoprene fermentation [20], YJM29 was utilized in α-pinene biosynthesis [21] and FHR-2 (E. coli BL21 (DE3) (pACYDuet-1-mvaE-mvaS-GPPS2-QH6, pTrcHis2B-ERG8-ERG12-ERG19-IDI1) was applied for β-pinene production [22]. The fermentation procedure was carried out as reported in the previous study [23] with some modifications.…”
Section: Biosynthesis and Analysis Of Isoprenoids Using The Engineerementioning
confidence: 99%
“…Optical density (OD) of the bacteria was measured with a spectrophotometer (Cary-50, Varian Inc. USA) at a wavelength of 600 nm. The isoprene, α-pinene and β-pinene production were analyzed as described earlier [20][21][22] by a gas chromatograph (GC) equipped with a flame ionization detector (FID) and a HP-1 column (30 m×0.25 mm×0.25 μm, Agilent). The concentration of target production was calculated with peak area on the bases of a standard curve.…”
Section: Biosynthesis and Analysis Of Isoprenoids Using The Engineerementioning
confidence: 99%